Vyakaranshastrey Siddhantkaumdha Anivaryatvam: Exploring the Necessity of Vyakaranshastrey Siddhantkaumdha in Vedas (Journal of Advances and Scholarly Researches in Allied Education, 2011)
यो वेद वेद वदनं  सदनं हि सम्यक् ब्राह्यस्सवेदमपि वेद  किमन्यशास्त्रम्।